The Role of Vocational Identity as a Mediator in the Relationship between Parental Career-Related Behavior and Career Decision-Making Process - Eveline, Eveline; Dewi, Francisca Iriani Roesmala; Hutapea, Bonar (UI Scholars Hub, 2015)
Career decision-making process (CDMP) is an individual skill in determining career decisions. During crisis development, transition-exploration adolescent may have difficulty in determining career goals. Two aspects stabilizer CDMP i.e.vocational identity ([VI], internal aspect) and parents’ involvement in adolescent career issues (external aspect). This study investigated parental involvement in three forms (support, interference, lack of engagement) of the variable parental career-related behaviors (PCB). Based on previous research, the VI role to CDMP can be enhanced through the positive role parents. Therefore, this research investigated the VI role as a mediator in the PCB and CDMP relationship, each VI or PCB role directly to CDMP, and PCB role to IV. Research subjects of first semester ( 19 years) students from a private university in Lippo Village-Tangerang were selected through simple random sampling. Data were analyzed with SPSS Amos v.22. Multivariate regression in path analysis showed the theoretical model of each form of PCB did fit with the empirical data. VI has a direct role to CDMP (38.00, 32.00, and 35.00%). Every form of PCB shows a direct role to CDMP (19.00, -13.00, and -15.00%). PCB interference and lack of engagement contribute to VI at -23.00 and -15.00%. VI of each PCB form shows no role as a mediator in the PCB and CDMP relationship on exploration-transition university students.